Identifikasi dan Tingkat Serangan Ulat Api pada Perkebunan Kelapa Sawit Belitung Timur - Jonathan, Ahmad; Apriyadi , Rion; Saputra3, Herry Marta (Penerbit Goodwood, 2025)
Purpose: This study aimed to obtain data on the presence of caterpillars and the level of attack on oil palm plantations in East Belitung Regency. Methodology: The research will be conducted from June to August 2024. The study was conducted in oil palm plantation areas in East Belitung Regency. The research method used an exploratory method with purposive sampling. There were 5 sub districts where the survey was conducted: Gantung, Simpang Pesak, Dendang, Simpang Renggiang, and Kelapa Kampit. Each sub-district selected to 2-3 oil palm plantations that had already produced (TM). Fifty oil palm trees were sampled from each plantation, totaling 750 samples. Result: The results showed that the caterpillar species found in East Belitung were Darma tirma and Olona gateri. The abundance of caterpillars in East Belitung is very low, and the number of caterpillars found per plant is <2 per plant after pesticide application. Conclusion: The level of damage caused by fireworm pests in oil palm plantations in East Belitung was classified as low, with a light attack category. Limitations: This study focused on collecting data on fireworm attacks and identifying fireworms that attack oil palm plantations in East Belitung. Contribution: The research of this study are expected to be a reference in taking action to prevent and/or overcome fireworms pest attacks on oil palm plantations in East Belitung Regency.